Intraspecific variability of Holostylis reniformis: concentration of lignans, as determined by maceration and supercritical fluid extraction (SFE-CO2), as a function of plant provenance and plant parts - Martins, Gislaine F. [UNESP]; Pereira, Marcos D. P. [UNESP]; Lopes, Lucia Maria Xavier [UNESP]; Silva, Tito Da; Rosa, Paulo De T. Vieira E; Barbosa, Fernanda P.; Messiano, Gisele B.; Krettli, Antoniana U. (Sociedade Brasileira de Química, 2014)
Maceration and supercritical fluid extraction were used to prepare extracts from parts of plants (Holostylis reniformis) collected in two different regions of Brazil. ¹H NMR, HPLC-DAD-ESI/MS, HPLC-DAD, GC-MS, and chemometric techniques were used to analyse lignans in the extracts and showed that yields of SFE-CO2 were less than or equal to those of hexane maceration extracts. These analyses, in conjunction with the concentrations of aliphatic hydrocarbons, fatty acids and their methyl and ethyl derivatives in the extracts, also allowed the chemical composition of parts and provenance of the plant to be differentiated.
Keywords: Holostylis reniformis; Aristolochiaceae; lignans